The validity of n-alkanes to estimate intake and digestibility in Nellore beef cattle fed a tropical grass (Brachiaria brizantha cv. Marandu) - Morais, J. A. S. [UNESP]; Berchielli, Telma Teresinha [UNESP]; de Vega, A.; Queiroz, M. F. S. [UNESP]; Keli, A.; Reis, R. A. [UNESP]; Bertipaglia, L. M. A. [UNESP]; Souza, S. F. [UNESP] (Elsevier B.V., 2011)
The objective of the present experiment was to evaluate the ability of n-alkanes to estimate dry matter (DM) intake (DMI) and digestibility (DMD) in Nellore beef cattle fed a tropical grass cut at two growth stages (30 or 60 days). The effect of two different faecal sampling procedures (daily pool-Total- or rectal spot-Spot-samples) was also tested. Differences in faecal concentration between sampling methods were lower than 2% and 0.7% for 30-d and 60-d old grass, respectively, with slightly higher values in Spot samples. Faecal recoveries were not affected by the grass growth stage, except in the cases of C(31), C(33), and C(35) (P < 0.05), which were lower for 30-d compared to 60-d. There was lower ratio (P < 0.05) between internal and external recovery alkane pairs C(31)/C(32), C(33)/C(32) and C(35)/C(36) in treating 30-d treatment than in 60-d old grass. Faecal recovery of natural alkanes increased with chain length, recoveries up to 77.0% (C(35)), whereas dosed alkanes C(28), C(32) and C(36) showed average recoveries of 94.2%, 97.2% and 86.8%, respectively. Estimates of DMI were different from current values (P < 0.05) when used C(31)/C(32). C(33)/C(32) and C(35)/C(36) natural/dosed alkane pairs, regardless of the sampling procedure. An exception was the DMI estimated using the C(35)/C(36) alkane pair of the samples of total sampling, which does not differ from the actual values (P > 0.05). However, using recovery-corrected faecal concentrations reduced the differences between observed and estimated values (P > 0.05). Similarly, the DMD was underestimated with the alkanes C(31). C(33) and C(36), regardless of the method of sampling. Observed effect of forage development stage in the estimates of DMD (P < 0.05), (lower values for 30-d treatment were observed than in the 60-d), due to lower faecal recovery of alkanes in the 30-d treatment. By correcting the concentrations of alkanes with the faecal recovery of the individual alkane, the differences between the estimated and actual values were canceled (P > 0.05), regardless of age of forage, the alkane used or the sampling method. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: n-alkanes; Beef cattle; Markers; Palisade grass; Stage growth